Acid Plant And Converter Operation At The Mines Gaspe Smelter Using A Single Operating Peirce-Smith Converter - George Kachaniwsky (The Minerals, Metals and Materials Society, 1983)
Until mid-1982 the Mines Gaspe copper smelter consisted of a fluid bed roaster, a reverberatory furnace, two Peirce-Smith converters of which only one was blowing at any one time, anode casting facilities, and a single contact sulphuric acid plant treating both roaster and converter gases. Reduced concentrate supplies have led to the shutdown of the roaster and, as a result, it was necessary to adapt the converter and acid plant operation to the new operating mode: green concentrate smelting with resulting lower matte grades and acid plant treatment of off-gases from only one blowing converter. Therefore, modifications were carried out to existing equipment and methods of operation and control. This paper describes the result of work done to obtain steady, maximum strength, converter off-gas flow and an efficient acid plant operation. Topics covered include: optimization of converter operation, tightness of hood and off-gas ducting, improvements in acid plant/converter communications and modifications of acid plant operation and control to cope with the fluctuations in converter gas flowrates and strengths.